2020
DOI: 10.1002/adfm.202000941
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable Polyanhydrides as Encapsulation Layers for Transient Electronics

Abstract: Bioresorbable electronic systems represent an emerging class of technology of interest due to their ability to dissolve, chemically degrade, disintegrate, and/or otherwise physically disappear harmlessly in biological environments, as the basis for temporary implants that avoid the need for secondary surgical extraction procedures. Polyanhydride‐based polymers can serve as hydrophobic encapsulation layers for such systems, as a subset of the broader field of transient electronics, where biodegradation eventual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
78
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 82 publications
(104 citation statements)
references
References 32 publications
1
78
0
Order By: Relevance
“…Figure 1A highlights the design aspects and key materials for a simple system of this type, consisting of a polymer reservoir, a wireless power harvester, and a metal gate valve. Polybutanedithiol 1,3,5-triallyl-1,3,5-triazine-2,4,6(1 H ,3 H ,5 H )-trione penteonic anhydride (PBTPA), a bioresorbable polyanhydride ( 13 ), serves as a substrate and a containment vessel for an aqueous drug of interest. Synthesis of the PBTPA relies on thiol-ene click reactions of three compounds initiated by exposure to ultraviolet (UV) light: 4-pentenoic anhydride (4PA), 1,3,5-triallyl-1,3,5-triazine-2,4,6(1H,3H,5H)-trione (TTT), and 1,4-butanedithiol.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 1A highlights the design aspects and key materials for a simple system of this type, consisting of a polymer reservoir, a wireless power harvester, and a metal gate valve. Polybutanedithiol 1,3,5-triallyl-1,3,5-triazine-2,4,6(1 H ,3 H ,5 H )-trione penteonic anhydride (PBTPA), a bioresorbable polyanhydride ( 13 ), serves as a substrate and a containment vessel for an aqueous drug of interest. Synthesis of the PBTPA relies on thiol-ene click reactions of three compounds initiated by exposure to ultraviolet (UV) light: 4-pentenoic anhydride (4PA), 1,3,5-triallyl-1,3,5-triazine-2,4,6(1H,3H,5H)-trione (TTT), and 1,4-butanedithiol.…”
Section: Resultsmentioning
confidence: 99%
“…Preparation of the materials began with mixing of 4-PA, TTT, and 1,4-butanedithiol with a molar ratio of 1:4:7 (PBTPA 1:4:7) or 1:1:2.5 (PBTPA 1:1:2.5) in polydimethylsiloxane (PDMS) molds. Initiating a thiol-ene click reaction by adding photoinitiator (5 weight %) and exposing to UV light (λ = 365 nm) formed PBTPA for the bioresorbable reservoirs ( 13 ). Wet etching of foils (Mg foil, 10 to 50 μm thick; or Mo foil, 10 μm thick) yielded bioresorbable metal electrodes.…”
Section: Methodsmentioning
confidence: 99%
“…However, it must be noted that some applications only require stable biotic-abiotic interfaces for a certain period of time (Muskovich and Bettinger, 2012 ; Lu et al, 2020 ). In the area of biodegradable encapsulation, Choi et al ( 2020 ) demonstrated a bioresorbable polyanhydride-based polymer (PBTPA). The result shows PBTPA film has good biocompatibility, low swelling during dissolution in water, mechanical properties supporting robust operation in flexible devices, and good processability potential.…”
Section: Packaging and Substrate Materialsmentioning
confidence: 99%
“…As shown in Fig. 2a , extending the in vivo operational lifetime of bioresorbable electronic stimulators from a few days to several months demands solutions to daunting challenges in materials science and device design that follow directly from requirements that the system must be (1) electrically reliable in operation, with minimal permeation of biofluids and parasitic leakage of current 26 30 , (2) mechanically robust under various deformations, including stretching, twisting and bending, during natural motions 31 , (3) completely dissolvable (i.e., bioresorbable), at the materials level, without adverse effect 32 , and (4) entirely biocompatible during and after the treatment duration 23 . The operational lifetimes reported here are significantly longer than those of previously reported flexible or stretchable bioresorbable devices, where the operation is limited typically to a few days (Supplementary Note 2 ) 15 , 33 35 .…”
Section: Resultsmentioning
confidence: 99%